The burst of electrophysiological signals in the suprachiasmatic nucleus of mouse during the arousal detected by microelectrode arrays - Yiding Wang; Yiding Wang; Yilin Song; Yilin Song; Yuchuan Dai; Yuchuan Dai; Xinrong Li; Xinrong Li; Jingyu Xie; Jingyu Xie; Jinping Luo; Jinping Luo; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
The neural mechanisms of torpor have essential reference significance for medical methods and long-term manned space. Changes in electrophysiology of suprachiasmatic nucleus (SCN) conduce to revealing the neural mechanisms from the torpor to arousal. Due to the lower physiology state during the torpor, it is a challenge to detect neural activities in vivo on freely behaving mice. Here, we introduced a multichannel microelectrode array (MEA) for real-time detection of local field potential (LFP) and action potential (spike) in the SCN in induced torpor mice. Meanwhile, core body temperature and behaviors of mice were recorded for further analysis. Platinum nanoparticles (PtNPs) and Nafion membrane modified MEA has a lower impedance (16.58 ± 3.93 kΩ) and higher signal-to-noise ratio (S/N = 6.1). We found that from torpor to arousal, the proportion of theta frequency bands of LFPs increased, spike firing rates rapidly increased. These results could all be characteristic information of arousal, supported by the microscopic neural activity promoting arousal in mice. MEA displayed real-time dynamic changes of neuronal activities in the SCN, which was more helpful to analyze and understand neural mechanisms of torpor and arousal. Our study provided a factual basis for the neural state in SCN of induced non-hibernating animals, which was helpful for the application of clinics and spaceflight.